Indicators of real convergence and their application - Eugen Stefan Pecican (Romanian Academy, National Institute for Economic Research, 2010)
Measurable aspects of the economic convergence of EU countries form the main topic of this paper. For this purpose, statistical and econometric methods are presented and applied for revealing characteristic elements of such a process. A first group of methods refers mainly to aspects such as: homogeneity, polarisation or EU countries' concentration by GDP per capita at different stages. A second group of methods refers to the intensity of several correlated processes that could ensure favourable conditions for achieving economic convergence such as: initial stage of development, evolutions in time, EU's general development, territorial cooperation. Romania's situation in the context of EU countries' convergence is the prevailing topic.
Keywords: O47; C21; C22; C43; C53; 330; dispersion; variation coefficient; concentration coefficient; Lorentz curve; regression model; β-coefficient; integrated and co-integrated series; matrix of transition probabilities; territorial interdependence; territorial index; growth index; territorial econometrics